Manufacturing and services interactions in international trade and global value chains - Stare, Metka (Teorija in praksa, 2019)
We explore patterns and trends in interactions involving manufacturing and services in international trade based on trade in value added data. The analysis results show a weak upward trend in the intensity of links between services and manufacturing from 2000 to 2014 in the EU. Foreign services gained in importance in the value added of manufacturing exports across all EU economies, and relatively more in new EU member states, including Slovenia. The analysis points to the dominant role played by services in international business processes, holding implications for public policies, firms' strategies and the directions of future research.
Keywords: Dodana vrednost; Export; gospodarska diplomacija; International trade; Izvoz; Manufacturing industries; Mednarodna trgovina; Predelovalna industrija; Services; Storitve; Value added